Nonzero Berry phase in quantum oscillations from giant Rashba-type spin splitting in LaTiO(3)/SrTiO(3) heterostructures - Veit, M. J. (Nat Commun, 2018)
The manipulation of the spin degrees of freedom in a solid has been of fundamental and technological interest recently for developing high-speed, low-power computational devices. There has been much work focused on developing highly spin-polarized materials and understanding their behavior when incorporated into so-called spintronic devices. These devices usually require spin splitting with magnetic fields. However, there is another promising strategy to achieve spin splitting using spatial symmetry breaking without the use of a magnetic field, known as Rashba-type splitting. Here we report evidence for a giant Rashba-type splitting at the interface of LaTiO(3) and SrTiO(3). Analysis of the magnetotransport reveals anisotropic magnetoresistance, weak anti-localization and quantum oscillation behavior consistent with a large Rashba-type splitting. It is surprising to find a large Rashba-type splitting in 3d transition metal oxide-based systems such as the LaTiO(3)/SrTiO(3) interface, but it is promising for the development of a new kind of oxide-based spintronics.